PENGARUH STRUKTUR KEPEMILIKAN SAHAM, STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DU BURSA EFEK INDONESIA - Marsinah Marsinah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
The aim of this research is to determine the influence of leadership and communication on work productivity of employees of AKPER KESDAM II/Sriwijaya Palembang. The samples used in this study were 39 employees. Data collection techniques were carried out by distributing questionnaires to employees of AKPER KESDAM II/Sriwijaya Palembang. This discussion provides information that leadership (X1) and communication (X2) simultaneously affect work productivity (Y). real or significant to the work productivity of employees of AKPER KESDAM II/Sriwijaya Palembang. From the multiple linear regression equation, we get Y=20.931+ 0.456 + 0.333 X2 + e, which means work productivity (Y) is influenced by leadership (X1) and communication (X2). The coefficient of determination (R2) between leadership (X1) and communication (X2) on work productivity (Y) Adjusted R square = 0.545 means that 54.5% of work productivity variables (Y) are influenced by leadership (X1) and communication (X2) and the remaining 45.5% is influenced by other variables